Decephring the toxicity of polycyclic aromatic hydrocarbons in HepG2 cell line - Morgado, Patrícia I. (2018)
Polycyclic Aromatic Hydrocarbons (PAHs) are persistent pollutants present in the environment with known mutagenic and carcinogenic properties. In the present study the effect of exposure to single or multiple doses of benzo[a]anthracene (BaA), pyrene (Pyr) and three HPAHs (1-ClPyr; 1-BrPyr and 7-ClBaA) were evaluated in a liver-derived human cell line (HepG2). Cytotoxicity as accessed by the classic MTT and neutral red showed a mild toxic effect in response to single or multiple dose exposure for up to 72h; except for multiple dose exposure to BaA and 7-ClBaA (cumulative concentration of 4 µM) and single exposure to 10 µM BaA. Furthermore, a selective mitochondrial and lysosomal toxicity was observed for Pyr and BaA series, respectively. In order to understand the underlying molecular mechanisms responsible for this effect, ROS production, mitochondrial membrane depolarization, lysosomal pH, DNA fragmentation and apoptosis mediators were evaluated after exposure to single PAHs doses. All compounds were able to trigger oxidative stress after 24h as measured by catalase activity and a good correlation was found between mitochondrial membrane depolarization, lysosomal pH increase and MTT and neutral red assays, respectively. The evaluation of cell death mediators showed that caspase-3/7 but not anexin-V pathways were involved in toxicity triggered by the studied compounds. In conclusion, the studied PAHs, especially 1-BrPyr and BaA, exhibit cytotoxic effects when accumulated, and may have adverse effects to humans after long periods of exposure.